Apa yang Mendorong Intensi Perilaku Konservasi Hutan dan Lingkungan Masyarakat Indonesia di Ranah Publik? - Ulayya Yassar Widyasa; Ikhsan Fuady; Kunto Adi Wibowo; Detta Rahmawan (Humanitas (Jurnal Psikologi), 2026)
Pro-environmental behavior in communal spaces remains a challenge in Indonesia, particularly in bridging individual concerns with actual behavior. This study examines how models influence individual intentions toward environmental behavior in the public sphere. This study uses an extended theoretical framework of the Theory of Reasoned Action (TRA) through the inclusion of environmental responsibility as a contextual dimension. This study was designed as a quantitative study with a survey method. Survey data were obtained from 80 Indonesian respondents using an 18-item closed-ended questionnaire, and analyzed using Structural Equation Modeling (SEM). The model estimates showed acceptable fit with the observed data (RMSEA = 0.049; CFI and TLI = 0.94; NNFI = 0.93). The findings indicate that attitudes toward environmental behavior in the public sphere and subjective norms do not influence individual intentions to engage in pro-environmental behavior in the public sphere. Meanwhile, environmental responsibility has an influence on intentions for pro-environmental behavior in the public sphere. Other findings indicate that intentions have a significant influence on pro-environmental behavior in the public sphere. These findings indicate that to increase pro-environmental intentions and behavior in the public sphere, it is necessary to increase environmental responsibility in society.